Evaluation of total phenolic content and antioxidant activity in aqueous and ethanolic extracts of leucosyke capitellata - An Nashroh binti Dahlan; Mardani Abdul Halim; Zainul Amiruddin Zakaria; Ruzaidi Azli Mohd Mokhtar (Penerbit UMS, 2024)
Leucosyke capitellata is rich in tannins, steroids, and flavonoids and has been traditionally used in the Philippines and Sabah, Malaysia, for treating inflammation, hypertension, and diabetes. However, scientific research on L. capitellata remains limited. This study aims to investigate the total phenolic content (TPC) and antioxidant potential of the aqueous and ethanolic extracts from the leaves, roots, and stems of L. capitellata. The TPC was measured using the Folin-Ciocalteu method, and the antioxidant activity was assessed through DPPH scavenging. Among the extracts, the ethanolic root extract exhibited the highest TPC (135.655 ± 0.045 mg GAE/g). All extracts demonstrated significant antioxidant activity (IC50 < 50 μg/mL), with the leaves aqueous extract showing the highest antioxidant activity (IC50 = 5.274 μg/ mL) despite having a relatively low TPC (37.737 ± 0.013 mg GAE/g). This discrepancy between TPC and antioxidant activity highlights the complex nature of plant extracts and suggests that factors beyond TPC contribute to their antioxidant mechanisms. These findings indicate that L. capitellata is a promising source of natural antioxidants.